Learning English Listening Using Media Busuu Application - Lina, Lina Rahmawati; Hidayat, Hendi (STIT Buntet Pesantren Cirebon, 2024)
Changes to the kurikulum 2013 into a kurikulum merdeka, a form of a new approach to the curriculum in Indonesia. The independent curriculum frees schools to develop curricula according to the context and needs of students in each region. But in reality, pedagogy in Indonesia still focuses on traditional methods. This research develops digital learning resources for writing report text referring to the CEFR national standard for junior high school students. The method used is the research and development model of R&D by Borg & Gall. The stages of this research began with needs analysis, design and development of writing learning resource websites. This study develops an innovative prototype for learning to write an English report text. It is hoped that this research can be used in the current curriculum as a reference for the development of digital writing resources with reference to CEFR international standards that suit the needs of students in each region.